Improvement in acupoint selection for acupuncture of nerves surrounding the injury site: electro-acupuncture with Governor vessel with local meridian acupoints - He, Guan-heng (Neural Regen Res, 2015)
Peripheral nerve injury not only affects the site of the injury, but can also induce neuronal apoptosis at the spinal cord. However, many acupuncture clinicians still focus only on the injury site, selecting acupoints entirely along the injured nerve trunk and neglecting other regions; this may delay onset of treatment efficacy and rehabilitation. Therefore, in the present study, we compared the clinical efficacy of acupuncture at Governor vessel and local meridian acupoints combined (GV/LM group) with acupuncture at local meridian acupoints alone (LM group) in the treatment of patients with peripheral nerve injury. In the GV/LM group (n = 15), in addition to meridian acupoints at the injury site, the following acupoints on the Governor vessel were stimulated: Baihui (GV20), Fengfu (GV16), Dazhui (GV14), and Shenzhu (GV12), selected to treat nerve injury of the upper limb, and Jizhong (GV6), Mingmen (GV4), Yaoyangguan (GV3), and Yaoshu (GV2) to treat nerve injury of the lower limb. In the LM group (n = 15), only meridian acupoints along the injured nerve were selected. Both groups had electroacupuncture treatment for 30 minutes, once a day, 5 times per week, for 6 weeks. Two cases dropped out of the LM group. A good or excellent clinical response was obtained in 80% of the patients in the GV/LM group and 38.5% of the LM group. In a second study, an additional 20 patients underwent acupuncture with the same prescription as the GV/LM group. Electomyographic nerve conduction tests were performed before and after acupuncture to explore the mechanism of action of the treatment. An effective response was observed in 80.0% of the patients, with greater motor nerve conduction velocity and amplitude after treatment, indicating that electroacupuncture on specific Governor vessel acupoints promotes functional motor nerve repair after peripheral nerve injury. In addition, electromyography was performed before, during and after electroacupuncture in one patient with radial nerve injury. After a single session, the patient's motor nerve conduction velocity increased by 23.2%, indicating that electroacupuncture at Governor vessel acupoints has an immediate therapeutic effect on peripheral nerve injury. Our results indicate that Governor vessel and local meridian acupoints used simultaneously promote functional repair after peripheral nerve injury. The mechanism of action may arise from an improvement of the local microenvironment in injured nervous tissue, as well as immediate effects of Governor vessel and local meridian acupoint stimulation to ensure the continuity between the peripheral and central nervous systems.